A preliminary estimation for CCS storage cost of Korea. Issue 1 (2nd January 2016) - Kim, Ji Whan; Choi, Jung Hyun
Abstract: Carbon capture and sequestration (CCS) projects can be considered a promising alternative for stabilizing carbon dioxide emissions in the atmosphere. There has been a lot of support from the Korean government to boost CCS projects, so that they may become commercialized. To conduct a CCS project, economic and geological considerations, as well as technical feasibility, are required. An excessively high cost prohibits CCS projects from being commercialized, even with the proper geological condition and technical feasibility. Therefore, it is essential to conduct an appropriate economic estimation analysis alongside the geological investigation and the technique development. The aim of this study is to estimate the storage costs of CCS projects, which are typically composed of capture, transport, and storage. Since cost estimation analyses have rarely been carried out in Korea, we have estimated the construction cost of the CCS storage by adopting assumptions made in the previous studies. To store 2.02 Mt for 20 years, 6.75–9.58 $/tCO2 is the estimated financial requirement.